1998
DOI: 10.1128/jvi.72.12.10003-10010.1998
|View full text |Cite
|
Sign up to set email alerts
|

Guanylyltransferase Activity of the LEF-4 Subunit of Baculovirus RNA Polymerase

Abstract: The baculovirus Autographa californica nuclear polyhedrosis virus encodes a DNA-dependent RNA polymerase that transcribes viral late genes. This polymerase is composed of four equimolar subunits, LEF-4, LEF-8, LEF-9, and p47. Here we present data indicating that the LEF-4 subunit of RNA polymerase is a guanylyltransferase. Incubation of RNA polymerase in the presence of divalent cation and radiolabeled GTP resulted in the formation of a covalent enzyme-guanylate complex that comigrated with the LEF-4 subunit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 30 publications
2
19
0
2
Order By: Relevance
“…The specific activities of the mutant and wild-type enzymes were determined within the linear range of enzymatic activity. With the wild-type enzyme, 0.5% of the available binding sites were radiolabeled, comparable to the level observed with native LEF-4 produced in baculovirus-infected cells (12). The activities of the triphosphatase mutants were equivalent to that of the wild-type protein, with the exception of that of E9/11A, which was 2.5-fold higher than the activity of the wild-type protein.…”
Section: Characterization Of the Rna Triphosphatase Component Of Lef-4supporting
confidence: 55%
See 4 more Smart Citations
“…The specific activities of the mutant and wild-type enzymes were determined within the linear range of enzymatic activity. With the wild-type enzyme, 0.5% of the available binding sites were radiolabeled, comparable to the level observed with native LEF-4 produced in baculovirus-infected cells (12). The activities of the triphosphatase mutants were equivalent to that of the wild-type protein, with the exception of that of E9/11A, which was 2.5-fold higher than the activity of the wild-type protein.…”
Section: Characterization Of the Rna Triphosphatase Component Of Lef-4supporting
confidence: 55%
“…RNA triphosphatase activity of RNA polymerase and purified LEF-4. We have previously shown that the LEF-4 subunit of AcNPV RNA polymerase has guanylyltransferase activity, suggesting that LEF-4 is an RNA capping enzyme (12). Furthermore, analysis of the LEF-4 amino acid sequence revealed homology to six motifs that are shared among viral and cellular guanylyltransferases in the C-terminal half of the protein.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations